Local Autonomy and Inter-Sector Performance-Based-Governance in Lampung Province - Ari Darmastuti (International Conference On Law, Business and Governance (ICon-LBG), 2013)
Paradigmatic shift in the management of local government in Indonesia, from a centralistic-authoritarian under New Order Era to a democratic-de-centralistic system under Reformation Era, demanded a shift in the system of evaluating institutional capacity of any local government in Indonesia. This paper intend to compare inter-sector performance-based institutional capacity of 3 regencies in Lampung using a ten inter-sector performances method developed by Sustainable Capacity Building for Decentralization, a project funded by Ministry of Home Affairs, Republic of Indonesia. Three separate surveys in three regencies in Lampung between 2007-2009 used ten inter-sector performances to evaluate institutional capacity of each regency. The data came from surveys used a 10% sample from population of all civil servants in each rank in the respective regency.This paper demonstrates that local government institutional capacities in Lampung Province have not only varied in terms of regional differences, but also in terms of sector differences. For the inter-sector performance, the poorest performance of the three regencies falls on inter-sector function of information and communication whilst the highest performance was on provision process of goods and services. Comparing the three regencies, the highest average of inter-sector performance-based institutional capacity of the three was East Lampung and North Lampung as the lowest, while South Lampung was the second. This paper then drew conclusion that the single recipe of symmetric decentralization needs to be replaced, or at least considered to be replaced with asymmetric decentralization which is more suitable with the varied local governmentsâ institutional capacities.